Do Microplastics in Soil Influence the Bioavailability of Sulfamethoxazole to Plants? - Anna Parus; Natalia Lisiecka; Arkadiusz Kloziński; Joanna Zembrzuska (Plants)
The presence of pharmaceuticals and MPs in soil raises concern due to their potential impact on plant health and ecosystem stability. This study investigates the impact of MPs on the bioavailability and phytotoxicity of sulfamethoxazole (SMX) using sorghum as a model plant. Three types of MPs—polyethylene (PE), polystyrene (PS), and acrylonitrile–butadiene–styrene copolymer (ABS)—were analyzed in primary and aged forms. The results indicate that MPs influence SMX sorption and desorption, affecting its bioavailability in soil. Low SMX concentrations (≤5 mg/kg) stimulated sorghum growth, while higher concentrations (≥25 mg/kg) significantly inhibited germination and biomass production. The presence of 1% MPs in soil generally reduced SMX toxicity, suggesting a role for MPs in modifying antibiotic availability in the soil matrix. Bioavailability analyses confirmed interactions between MPs and SMX or MPS and soil components, with variability depending on polymer type and ageing process. Among the tested MPs, polystyrene showed the strongest effect on increasing SMX bioavailability in both primary and aged forms. These findings highlight the environmental implications of MPs in agricultural soils, particularly concerning contamination, crop quality, and antibiotic resistance. A deeper understanding of MP–pharmaceutical interactions is crucial for evaluating long-term ecological risks and formulating effective mitigation strategies.